Understanding massive youth unemployment during the EU sovereign debt crisis: a configurational study - Marques, Paulo; Hörisch, Felix (Comparative European politics, 2020)
After the economic downturn of 2008, youth unemployment rose rapidly in the EU. Simultaneously, many countries were also facing increasing public deficits. In this context, the EU developed a set of policies to tackle youth unemployment and public debt. While policies to fight unemployment were underpinned by the concept of social investment, austerity was seen as the best way to reduce public debt. These different approaches to the crisis led to a growing tension between the two policy areas. This problem was particularly visible in the countries most affected by the sovereign debt crisis where youth unemployment remained very high for a long period of time. Not only were countries with high public debt and low growth unable to invest sufficiently in active labour market policies (ALMPs), but also, at the same time, austerity policies depressed the economic activity. This study uses the fsQCA methodology. Our results point to the existence of one necessary condition for high youth unemployment—low expenditure on ALMPs. The analysis of sufficient conditions points to the existence of one configuration: the countries most affected by the sovereign debt crisis and characterized by having a demand-led growth model, combined a low GDP growth with a low expenditure on ALMPs. Together, this led to high levels of youth unemployment.